10-Year Risk for Cardiovascular Disease Among Male Workers in Small-Sized Industries. Issue 3 (May 2015) - Park, Kyongok; Hwang, Seon Young
Abstract : Background: Health management or health promotion programs are limited, particularly for workers in small-sized industries. Objectives: This study aimed to identify the 10-year cardiovascular disease (CVD) risk using the general Framingham Risk Score and examine predictors of CVD risk adjusted for age among male workers. Methods: Routine health screening data and self-reported questionnaires were collected from 12 933 male workers in 1041 industries from 2009 to 2011 in South Korea. Results: The proportion of high CVD risk (Framingham Risk Score >20%) was 7.1% (n = 919). Most (83.5%) subjects were manufacturing workers, engaged in manual labor, with a mean (SD) age of 42.1 (9.2) years (range, 30–70 years). Younger workers were more likely to smoke cigarettes, drink alcohol heavily, and be physically inactive. A logistic regression analysis showed that after adjusting for age, occupation type, body mass index, physical activity, and alcohol consumption were significant predictors of 10-year CVD risk. Conclusion: To reduce CVD risk, education regarding lifestyle modification should be emphasized for small-sized industrial workers who are overweight, physically inactive, and heavy alcohol drinkers and who work as bus or taxi drivers. Careful attention is also needed for younger workers who are a latent risk group for the development of CVD.